Synthesis of Expanded Hetero 2, 6‐Pyrihexaphyrins. Issue 6 (5th February 2020) - Rawat, Nisha; Thorat, Kishor G.; Kumar, Sunit; Ravikanth, Mangalampalli
Abstract : New examples of expanded hetero 2, 6‐pyrihexaphyrins 2–6 were synthesized in 12–18 % yields by condensing one equivalent of [10, 10'‐bis( p ‐ tert ‐butylphenyl)hydroxymethyl]‐1, 3‐bis(2‐thienyl)‐pyridine diol with five different tripyrranes, under mild acid catalyzed conditions. The formation of 2, 6‐pyrihexaphyrins 2 –6 was confirmed by corresponding molecular ion peak in HR‐MS and were thoroughly characterized by 1D and 2D NMR spectroscopy, absorption, electrochemical and DFT/TD‐DFT studies. In 1 H NMR, the proton resonances were either upfield or downfield shifted as the nature of one of the core heterocycles was varied from pyrrole to furan, thiophene, selenophene, and tellurophene indicating that the electronic properties of the macrocycle were altered by changing the core heterocycle. The NMR studies indicated that the macrocycles were nonaromatic in nature and absorption spectra of 2, 6‐pyrihexaphyrins 2 –6 showed one broad absorption band in the region of 600–1000 nm and two relatively sharp bands in the region of 350–500 nm. The aza analogue 2 showed considerable red shift in the absorption bands compared to other hetero 2, 6‐pyrihexaphyrins 3 –6 . Upon protonation of the macrocycles, the resulting protonated macrocycles 2.H2 2+ ‐6.H2 2+ exhibits bathochromically shifted absorption bands. The redox studies indicated that the 2, 6‐pyrihexaphyrins 2 –6 are electron deficient and DFT studies supported the distortion and nonaromatic nature of the macrocycles. Abstract : A series of stable pyridine embedded expanded heteroporphyrinoids known as hetero 2, 6‐pyrihexaphyrins were synthesized and studied their properties by NMR, absorption, electrochemical and DFT techniques. The studies supported the nonaromatic nature of these macrocycles.